Hepatoprotective activity of aqueous extract of Balanites aegyptiaca L. Delile (Balanitaceae) roots bark - TRAORE Tata Kadiatou; Noufou Ouédraogo; Geoffroy G. Ouédraogo; Gilchrist A. L. Boly; Leïla M. E. W. Kabré; Ernest N Sombié; Jotham Y. N’Do; Salfo Ouédraogo; Marius Lompo; Sylvin Ouédraogo; André Tibiri; Innocent Pierre Guissou (International Journal of Phytomedicine, 2020)
Balanites aegyptiaca (L.) Del (Balanitaceae) is traditionally used for the treatment of various ailments such as syphilis, jaundice and liver disorders, epilepsy, ... This study was designed to evaluate acute toxicity and hepatoprotective effect of aqueous extract of Balanites aegyptiaca on CCl4 induced hepatotoxicity in rats. Methods: Acute toxicity was assessed with the extract at a dose of 2000 mg / kg bw. The extract at doses of 25, 50 and 100 mg / kg b.w. was orally administered respectively to CC14-induced hepatotoxicity (0.5 ml / kg) animals. Silymarin (100 mg / kg) was given as a reference. Biochemical parameters such as ALT, AST, PT, ALB and ALP were assayed as well as enzymatic antioxidant activities SOD, CAT and MDA. Nitrogen monoxide (NO) involved in inflammation was also measured. Results: Activities of liver marker enzymes, ALT, AST and ALP, total protein, albumin and showed a significant hepatoprotective effect. Regarding antioxidant enzymatic activities in vivo (SOD, CAT and MDA) of aqueous extract exhibited a significant effect showing increasing levels of SOD, CAT and reducing malondialdehyde (MDA) levels. The production of NO is significantly reduced compared to the batch intoxicated by CCl4. Conclusion: Balanites aegyptiaca is endowed with hepatoprotective properties that can be attributed to antioxidant potential which could justify its use in traditional medicine in liver disorders.